Hubungan Antara Faktor-Faktor Eksternal dengan Kejadian Penyakit Tuberkulosis pada Balita - Emita Ajis, Nenny Sri Mulyani, Dibyo Pramono (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Tuberculosis (TB) poses a health problem both in developed countries and in developing countries. It is estimated that 160 of 100.000 people present TB (+), and 15% of them are children. In Kuantan Singingi district, the eradication program of TB is carried out with DOTS strategy in accordance with WHO recommendation. However, the program is still prioritized for adult patients although under-five children are the high risk group to be infected with the disease. In the past three years there have been increased cases of the incidence of tuberculosis found in under-five children. Many factors are related to the increased incidence of TB.Objective: This study aims at investigating most dominant external factors that are related to the incidence of TB among under-five children.Method: This was an observational study with a case control study design. Samples were 218 persons consisting of 109 persons as case and 109 persons as control selected with purposive sampling. Case was taken from under-five TB patients that were diagnosed by a pediatrician and a physician in community health center while control was taken from patients presenting other diseases attending the community health center in the past 12 months. Data were gathered through interview and the measure of ventilation and the degree of humidity. The collected data were presented with frequency distribution table and were then analyzed using bivariate and multivariate analyses.Results: The multivariate analysis showed that variables that were related to the incidence of under-five TB were smoking with OR = 2.6372 (p=0.0026), contact history with the case of TB (+) with OR = 2.6284 (p=0.0026) and family’s socio-economic status with OR = 2.587 (p=0.0012).Conclusion: The contact history, smoking and low socio-economic status were the risk factors related to the incidence of TB among under-five children in Kuantan Singingi District so that the programs of health promotion and health and safe life behavior (PHBS) needed to be enhanced especially the hazardous danger of smoking for smokers and the program of active case finding as well as complete and holistic treatment for the patients with a free of charge system in the community health centers needed to be realized.Keywords: external factor of tuberculosis, under-five children.